2019
DOI: 10.1111/srt.12822
|View full text |Cite
|
Sign up to set email alerts
|

Using content‐based image retrieval of dermoscopic images for interpretation and education: A pilot study

Abstract: Recent advances in artificial intelligence (AI) and computer-aided decision support methods have produced various efficient ways to allow for learning about skin problems. 1 In particular, advances in machine learning have spurred novel retrieval algorithms and aroused interest in content-based image retrieval (CBIR) techniques, where computer vision methods are applied to search for similar images to a "query" image based on the content of the image and visual clues such as color, shape, and pattern, from lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Scientists have developed support systems such as the computer-aided diagnosis (CAD) system and content-based medical image retrieval (CBMIR) system to help radiologists interpret medical images. The most important benefit of CBMIR is that it aids radiologists in identifying similar medical images in recalling previous cases during diagnosis [5]- [7]. Many content-based medical image retrieval (CBMIR) systems are based on image similarity, whereby a user enters a query image, and the system responds by supplying the most similar image focused on a certain measure of similarity.…”
mentioning
confidence: 99%
“…Scientists have developed support systems such as the computer-aided diagnosis (CAD) system and content-based medical image retrieval (CBMIR) system to help radiologists interpret medical images. The most important benefit of CBMIR is that it aids radiologists in identifying similar medical images in recalling previous cases during diagnosis [5]- [7]. Many content-based medical image retrieval (CBMIR) systems are based on image similarity, whereby a user enters a query image, and the system responds by supplying the most similar image focused on a certain measure of similarity.…”
mentioning
confidence: 99%
“…2/14 studies evaluated whether models had learned human-interpretable features and found that they had indeed learned to detect relevant structures [48,49]. 3/14 studies (discussed in detail in Section 2.2) investigated humanemachine interaction in the context of XAI [17,50,51].…”
Section: Usage Of Xaimentioning
confidence: 99%
“…3/13 studies [17,50,51] investigated the influence of XAI, more precisely of two CBIR systems, on the predictive accuracy and confidence of human users: Sadeghi et al [51] evaluated the framework introduced by Tschandl et al [16] with regards to whether it improved the classification performance of 16 non-medical graduate students on a 4-class classification task (basal cell carcinoma, melanoma, nevus and seborrheic keratosis). In a more recent study, Sadgehi et al [50] analyse the predictive performance of 14 non-medical graduate students and additionally evaluate whether the students perceive the system as useful for educational purposes. Both studies find improvements in the predictive performance of the graduate students when assisted by the CBIR: from on average 10.31/20 (51.56%) correct predictions to 12.19/20 (60.94%, 9.38% improvement) [51] and from an average of 9.9/20 (49.5%) correct diagnoses to 14/20 (70%, 20.5% improvement) [50].…”
Section: Evaluation Of Xai With Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Most content-based medical image retrieval (CBMIR) systems are focused on image similarity, whereby a user enters a query image, and the system responds by presenting the most similar image focused on a certain similarity criterion, then, the results of the related image query are shown in descending order. The basic concept of any CBMIR method consists of two main steps or phases: extraction of the feature (offline phase) and calculation of similarity measures (online phase) [6][7][8]. Figure 1 shows the main and fundamental framework of a CBMIR system.…”
mentioning
confidence: 99%